When size matters: a novel compact Cas12a variant for in vivo genome editing - Bubeck, Felix; Grimm, Dirk (PLoS biology, 2024)
A new study characterizes and improves a novel small Cas12a variant before adapting it for in vivo genome editing by delivery via adeno-associated virus (AAV) vectors, showcasing the potential of small CRISPR systems and their compatibility with viral vectors.
Gesehen am 12.12.2024